A Comparative Study on Dye Degradation by Leaf and Root Extracts of Parthenium hysterophorus L - Shahi, Dipesh; Sapkota, Rajiv (International Journal of Applied Sciences and Biotechnology, 2018)
The use of different dyes and pigments is increasing with the increase in industrialization leading to the high production of effluent. The effluent contaminated with dyes and dye-stuff has harmful effects on public health and the environment. Thus, the treatment of effluent is essential. Biological approaches are gaining much interest due to their cost-effective and eco-friendly nature over various physicochemical methods for the treatment of dye-contaminated wastewater. This study highlights on the biodegradation of congo red and malachite green by using leaf and root extracts of Parthenium hysterophorus. The extract and the dye were mixed in the ratio of 1:2 and incubated at 40ºC for 90 minutes. Decolorization assay was performed using UV visible spectrophotometer which indicated that decolorization was due to degradation of dyes into non-colored metabolites. The leaves extract exhibited higher decolorizing activity than roots extract. The maximum decolorization for leaves extract was 55.8% (congo red) and 51.6% (malachite green). Furthermore, phytotoxicity test was carried out to determine the effect of dyes and their degradation metabolites on seed germination and seedling growth of chickpea (Cicer arietinum L). The germination percentage and seedling growth were more in degradation metabolites than untreated dyes, indicating less toxic nature of degradation metabolites. Hence, it can be inferred that P. hysterophorus extracts can be used to treat dye wastewater and treated wastewater can be used for irrigation. Int. J. Appl. Sci. Biotechnol. Vol 6(4): 327-331